Structural Model of Health-Promoting Lifestyle based on Self-Compassion, Satisfaction and Frustration of Basic Psychological needs: The Mediating Role of Perceived Stress in Working Women - Maryam Nateghi; Shirin Kooshki; Mohtaram Nemattavousi (فصلنامه زن و جامعه)
Abstract Introduction: The aim of this study was to investigate the relationship between satisfaction and frustration of basic psychological needs and self-compassion with health promoting lifestyle, considering the mediating role of perceived stress in working women. Methods: This research was descriptive-correlation type. The statistical population of the research was all women working in government organizations and offices in Tehran province in 1401. Finally, in the present study, 400 women (168 single and 232 married) were randomly selected in a multi-stage manner, and they were given Basic Psychological Need Satisfaction and Frustration Scale, Self-Compassion Scale–Short Form, perceived stress Scale, and Profile Health-Promoting Lifestyle II answered. Findings: The results indicate that the fit indices obtained from the analysis support the acceptable fit of the structural model with the collected data. The relationship between perceived-stress and negative and meaningful health-promoting lifestyle, and the relationship between self-compassion and positive health-promoting lifestyle, and the relationship between satisfaction of basic psychological needs and positive and meaningful health-promoting lifestyle, and the relationship between failure to Basic psychological needs and health-promoting lifestyle were negative and significant. The indirect relationship between self-compassion and health-promoting lifestyle, on the one hand, the indirect relationship between satisfaction of basic psychological needs and health-promoting lifestyle, on the other hand, was positive and significant. Conclusion: The results showed that in working women, perceived-stress significantly mediates the relationship between basic psychological needs and self-compassion with health-promoting lifestyle.